2020
DOI: 10.1074/jbc.ra119.010467
|View full text |Cite
|
Sign up to set email alerts
|

Repression of sphingosine kinase (SK)-interacting protein (SKIP) in acute myeloid leukemia diminishes SK activity and its re-expression restores SK function

Abstract: Previous studies have shown that sphingosine kinase interacting protein (SKIP) inhibits sphingosine kinase (SK) function in fibroblasts. SK phosphorylates sphingosine producing the potent signaling molecule sphingosine-1-phosphate (S1P). SKIP gene (SPHKAP) expression is silenced by hypermethylation of its promoter in acute myeloid leukemia (AML). However, why SKIP activity is silenced in primary AML cells is unclear. Here, we investigated the consequences of SKIP down-regulation in AML primary cells and the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
3
1
Order By: Relevance
“…Primary AML cells have lower levels of SK1 and intracellular S1P and this can be reversed by re-expression of SKIP, concomitant with increased ceramide levels, and reduced ERK and increased apoptosis. Therefore, contrary to previous findings the downregulation of SKIP reduces SK1 activity in AML [116].…”
contrasting
confidence: 99%
“…Primary AML cells have lower levels of SK1 and intracellular S1P and this can be reversed by re-expression of SKIP, concomitant with increased ceramide levels, and reduced ERK and increased apoptosis. Therefore, contrary to previous findings the downregulation of SKIP reduces SK1 activity in AML [116].…”
contrasting
confidence: 99%
“…In addition to FAs and related metabolic pathways, sphingolipids also play a critical role in leukemogenesis by regulating the balance between cell proliferation and cell death ( 97 , 98 ). The formation and functionality of sphingolipids rely on oncogenic proteins including sphingosine kinases and acid ceramidases in AML cells.…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…Additionally, in line with potentially enhanced activity of SPHK1 in AML is the reduced expression of SKIP , a SPHK1 inhibitor, in primary AML cells [ 152 ]. However, while SKIP has been shown to inhibit SPHK function in fibroblasts [ 153 , 154 ], a study in K562 Chronic Myelogenous Leukemia cells reported that SKIP acts more as a positive, rather than negative, regulator of SPHK1/S1P [ 155 ]. Moreover, it was also found that primary AML cells showed decreased SPHK1 and SPHK2 activity, as measured by the conversion of d17-Sph into d17-S1P [ 155 ].…”
Section: Sls In Hematological Malignanciesmentioning
confidence: 99%
“…However, while SKIP has been shown to inhibit SPHK function in fibroblasts [ 153 , 154 ], a study in K562 Chronic Myelogenous Leukemia cells reported that SKIP acts more as a positive, rather than negative, regulator of SPHK1/S1P [ 155 ]. Moreover, it was also found that primary AML cells showed decreased SPHK1 and SPHK2 activity, as measured by the conversion of d17-Sph into d17-S1P [ 155 ]. Ultimately, additional studies are needed to conclusively address whether the levels of SPHK1/S1P are different in AML cells, perhaps by stratification of AML types and/or level/types of resistance.…”
Section: Sls In Hematological Malignanciesmentioning
confidence: 99%